Assessment of Prescription Errors among Community Pharmacists in Quetta Balochitsan, Pakistan - Najam, Sherjeel; Ul Haq, Noman; Saood, Muhammad; Nasim, Aqeel; Danish, Zeeshan; Shah, Yasmin; Andleeb, Shabana (Journal of Pharmacy Practice and Community Medicine)
Background: Community pharmacists can serve as a key source of scientifically correct drug information and can provide advice on how to utilise pharmaceuticals in a safe, appropriate, and cost–effective manner. The dispensing procedure at a community pharmacy is an important aspect of safe medication usage, and it is one of a pharmacist’s primary professional tasks, along with patient counselling. Objectives: To f ind awareness level of community pharmacist regarding prescription error and to find either they can find prescription errors or not. Methods: A cross sectional descriptive study was conducted in community pharmacies of Balochistan, Quetta by using simulated prescriptions containing identifiable errors in Quetta Pakistan. Analyses was performed on IBM SPSS. Results: As per qualifications the maximum 259 (92.8%) were Pharm-D degree holder. As far s experience is concerned most of them 197 (70.6%) had 1-3 years of experience. In all prescriptions Level of Errors Identification on individual Medicine. The result it was found that non identified errors were dominant in all prescription. Only the experience group was statistically significant (p<0.001). and rest of variables were non-significant (p>0.05). Conclusion: Understanding the types of prescription mistakes and the variables that contribute to them allows for error avoidance at the earliest stage of the pharmaceutical process. Preparing pharmacy, medical, and nursing students to recognise prescription mistakes enhances patient care and reduces the risk of negative outcomes.
Keywords: Prescription error; Community pharmacist; Pakistan